Identifikasi Faktor Eksternal Yang Mempengaruhi Motivasi Belajar Siswa di SMP Negeri 9 Kota Jambi - Niken Maharani Putri; Nelyahardi Gutji; Fellicia Ayu Sekonda (Journal on Education, 2023)
Motivation is a concept used to describe the initiation, direction, and intensity of individual behavior. Motivation is the force that drives someone to do something to achieve a goal. Internal factors are factors driving desires from within while external factors are factors driving desires from outside oneself. Such as encouragement from family environmental factors, school environmental factors, and community environmental factors. Factors that play a very important role in influencing student learning motivation are external factors. This study aims to look at the external factors that influence student learning motivation at SMP Negeri 9 Jambi City along with their indicators. This type of research is descriptive, the population for the assessment is students at SMP Negeri 9 Jambi City, totaling 75 students who are all used as research samples. The sampling technique used in this research is purposive sampling technique. The data collection tool in this study was a questionnaire containing 26 statement items. The data obtained is processed using percentage analysis techniques. Some students stated that external factors influenced student learning motivation at SMP Negeri 9 Jambi City on the family factor indicator with a percentage value of (59.2%). Some students stated that external factors influenced student learning motivation at SMP Negeri 9 Jambi City on the school factor indicator with a percentage value of (64.6%). Some students stated that external factors influenced student learning motivation at SMP Negeri 9 Jambi City on the community factor indicator with a percentage value of (59.1%). The results of the research based on the average percentage of the frequency of respondents' answers from 26 statement items show 61.2% of external factors that influence student learning motivation at SMP Negeri 9 Jambi City